Compassion Focused Group Therapy for People With a Diagnosis of Bipolar Affective Disorder: A Feasibility Study - Gilbert, Paul; Basran, Jaskaran K.; Raven, Joanne; Gilbert, Hannah; Petrocchi, Nicola; Cheli, Simone; Rayner, Andrew; Hayes, Alison; Lucre, Kate; Minou, Paschalina; Giles, David; Byrne, Frances; et al. (Frontiers in Psychology, 2022)
Background Compassion focused therapy (CFT) is an evolutionary informed, biopsychosocial approach to mental health problems and therapy. It suggests that evolved motives (e.g., for caring, cooperating, competing) are major sources for the organisation of psychophysiological processes which underpin mental health problems. Hence, evolved motives can be targets for psychotherapy. People with certain types of depression are psychophysiologically orientated towards social competition and concerned with social status and social rank. These can give rise to down rank-focused forms of social comparison, sense of inferiority, worthlessness, lowered confidence, submissive behaviour, shame proneness and self-criticism. People with bipolar disorders also experience elevated aspects of competitiveness and up rank status evaluation. These shift processing to a sense of superiority, elevated confidence, energised behaviour, positive affect and social dominance. This is the first study to explore the feasibility of a 12 module CFT group, tailored to helping people with a diagnosis of bipolar disorder understand the impact of evolved competitive, status-regulating motivation on their mental states and the value of cultivating caring and compassion motives and their psychophysiological regulators. Methods Six participants with a history of bipolar disorder took part in a CFT group consisting of 12 modules (over 25 sessions) as co-collaborators to explore their personal experiences of CFT and potential processes of change. Assessment of change was measured via self-report, heart rate variability (HRV) and focus groups over three time points. Results Although changes in self-report scales between participants and across time were uneven, four of the six participants consistently showed improvements across the majority of self-report measures. Heart rate variability measures revealed significant improvement over the course of the therapy. Qualitative data from three focus groups revealed participants found CFT gave them helpful insight into: how evolution has given rise to a number of difficult problems for emotion regulation (called tricky brain) which is not one’s fault; an evolutionary understanding of the nature of bipolar disorders; development of a compassionate mind and practices of compassion focused visualisations, styles of thinking and behaviours; addressing issues of self-criticism; and building a sense of a compassionate identity as a means of coping with life difficulties. These impacted their emotional regulation and social relationships. Conclusion Although small, the study provides evidence of feasibility, acceptability and engagement with CFT. Focus group analysis revealed that participants were able to switch from competitive focused to compassion focused processing with consequent improvements in mental states and social behaviour. Participants indicated a journey over time from ‘intellectually’ understanding the process of building a compassionate mind to experiencing a more embodied sense of compassion that had significant impacts on their orientation to (and working with) the psychophysiological processes of bipolar disorder.